2008
DOI: 10.1177/002214650804900202
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Asthma Prevalence: The Role of Housing and Neighborhood Environments

Abstract: This article examines the prevalence of asthma among New York City households from 10 racial/ethnic groups, and it explores whether differential exposure to potentially adverse housing and neighborhood conditions helps to mediate observed disparities. After adjusting for household size, Puerto Rican households exhibit the highest levels of asthma, followed by other Hispanic and black households. Mexican, Chinese, and Asian Indian households exhibit the lowest levels of asthma. Results from multilevel logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 40 publications
3
55
1
Order By: Relevance
“…42 However, as much as 40% of asthma in minority children has been attributed to exposure to residential allergens, and minority children have been found to live in homes that have high allergen levels, low indoor air quality, and live in environments with more air pollution. 43 Exposures to residential allergens also have been associated with living in urban environments of which the majority of this population is comprised of lower income minorities. 44 Our study found that the proportion of Non-Hispanic black and Puerto Rican children with asthma that reported receiving rental assistance was over seven times that of Non-Hispanic white children.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, as much as 40% of asthma in minority children has been attributed to exposure to residential allergens, and minority children have been found to live in homes that have high allergen levels, low indoor air quality, and live in environments with more air pollution. 43 Exposures to residential allergens also have been associated with living in urban environments of which the majority of this population is comprised of lower income minorities. 44 Our study found that the proportion of Non-Hispanic black and Puerto Rican children with asthma that reported receiving rental assistance was over seven times that of Non-Hispanic white children.…”
Section: Discussionmentioning
confidence: 99%
“…They are always among the first to adopt and reap the benefits of the latest life-saving medical technologies (Link et al 1998; Chang and Lauderdale 2009; Glied and Lleras-Muney 2009). SES is also positively associated with better material conditions, such as safe water, good sanitation, adequate nutrition and clothing, and well-built housing in safe neighborhoods away from toxic environments (Anderson and Armstead 1995; Evans and Katrowitz 2002; Rosenbaum 2008). Note, however, that with the growing prosperity of lower-SES groups and the continuing decline in the impact of infectious diseases on mortality, these material conditions are losing importance in the SES-mortality link, especially in developed countries.…”
Section: Theory and Evidencementioning
confidence: 99%
“…9 Research consistently suggests a complex interplay between individual (e.g., genetic predisposition), family (e.g., parental smoking, socioeconomic status, and maternal stress), and environmental risk factors (e.g., allergen exposure), which undermine asthma management and exacerbate vulnerability to poor outcomes. [10][11][12][13][14][15][16] Community violence, which may range from perceived threats to direct victimization, is one stressor that has an especially robust connection to asthma morbidity, as it is proposed to precipitate asthma exacerbations and result in increased healthcare utilization. 17,18 In a prospective study, adults with asthma who were exposed to violence had 92 times more asthma-related ED visits and 92 times more hospitalizations compared with adults without community violence exposure.…”
Section: Introductionmentioning
confidence: 99%